Orthodox Spirituality as the Ethical Basis of Poetics (The Meaning and Structure of Prayer in “Hariton” by Aleksandar Despotović) - Mumović, Ana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The paper examines Orthodox spirituality as the ethical basis of the poetics of Aleksandar Despotović (1933–2009), with special attention to the meaning and structure of prayer in his collection Hariton (2003). Within the complex notion of Orthodox spirituality, the analysis emphasizes the idea that God is reflected in human beings through actions and energies—an idea that permeates Despotović’s entire poetic oeuvre. This perspective shapes the ethical essence of the poet’s being and directs the thematic focus of his reflections on God, Kosovo, Orthodoxy, history and/or models of Serbian culture, and the concept of national identity.For a more nuanced and comparative interpretation of Despotović’s poetry in the light of Orthodox spirituality, the paper juxtaposes the image of Hilandar in the poetry of Miodrag Pavlović (1928–2014)—a leading Serbian poet, an outstanding connoisseur of Serbian and European poetry, a brilliant essayist, and one of the most influential voices of post-war Serbian literature—as well as in the poetry Slobodan Kostić (1952–2012), and Radomir Stojanović (1942), a poet from Kosovo and Metohija. Their intertextual resonances are considered not to equate the poetic achievements of distinct authors, but to demonstrate how prayer, Hilandar, or Saint Sava evoke similar spiritual experiences in Orthodox beings shaped by this tradition.The overview of Despotović’s Orthodox spirituality shows that, throughout all phases of his creative work, he remained steadfast in his faith in God and divine love, embraced the Bible as God’s revelation, and drew from it the source of his poetry and devotion.
Keywords: Aleksandar Despotović; Orthodox spirituality; worship; prayer; Kosovo and Metohija; Miodrag Pavlović; Slobodan Kostić; Radomir Stojanović